2021
DOI: 10.3390/nu13082521
|View full text |Cite
|
Sign up to set email alerts
|

A Convergent Functional Genomics Analysis to Identify Biological Regulators Mediating Effects of Creatine Supplementation

Abstract: Creatine (Cr) and phosphocreatine (PCr) are physiologically essential molecules for life, given they serve as rapid and localized support of energy- and mechanical-dependent processes. This evolutionary advantage is based on the action of creatine kinase (CK) isozymes that connect places of ATP synthesis with sites of ATP consumption (the CK/PCr system). Supplementation with creatine monohydrate (CrM) can enhance this system, resulting in well-known ergogenic effects and potential health or therapeutic benefit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 192 publications
(208 reference statements)
0
6
0
Order By: Relevance
“…The inhibitory effects of the soy-based diet on Akt and ERK could be mediated by genistein, known to inhibit Tyr kinases (for a review, see [54]) and to have an anti-proliferative effect, consistent with indirect AMPK activation [55][56][57][58][59]. The activation of Akt and ERK seen with Cr supplementation was also reported for skeletal muscle [60,61] and suggested by recent database meta-analysis [62]. Such rather pro-anabolic effects could mediate many cytoprotective aspects of Cr supplementation, such as in cardioprotection [18,19], muscular dystrophies, neuromuscular and neurodegenerative disorders [16,63], brain health [64], or wound healing [65].…”
Section: Discussionmentioning
confidence: 80%
“…The inhibitory effects of the soy-based diet on Akt and ERK could be mediated by genistein, known to inhibit Tyr kinases (for a review, see [54]) and to have an anti-proliferative effect, consistent with indirect AMPK activation [55][56][57][58][59]. The activation of Akt and ERK seen with Cr supplementation was also reported for skeletal muscle [60,61] and suggested by recent database meta-analysis [62]. Such rather pro-anabolic effects could mediate many cytoprotective aspects of Cr supplementation, such as in cardioprotection [18,19], muscular dystrophies, neuromuscular and neurodegenerative disorders [16,63], brain health [64], or wound healing [65].…”
Section: Discussionmentioning
confidence: 80%
“…Its administration results in increases in the total musculoskeletal creatine pool by around 25% (up to ≈37% if accompanied with physical exercise) [ 86 ] which benefits the athlete’s recovery time and improves athletic performance (increased strength, muscle mass, and power) [ 87 ]. It has been reported that the increase in muscle creatine after CrM supplementation might optimize the function of the creatine kinase/phosphocreatine system and subsequently benefit energy- and mechanical-dependent processes in different tissues [ 88 , 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, maintaining or increasing muscle creatine levels during periods of inactivity or recovery from injury may offer benefits [ 93 ]. Indeed, several studies have evaluated the potential effects of CrM supplementation during periods of immobilization [ 94 ] revealing: (i) Maintenance of muscle mass or cross-sectional area, muscle strength, and endurance; (ii) maintenance or increase in total muscle creatine concentration; (iii) maintenance of GLUT-4 concentration [ 95 ]; (iv) increased muscle glycogen; and (v) increased expression of growth factors (IGF-1) and myogenic regulatory factors [ 88 , 93 ]. However, it is difficult to draw definitive conclusions due to heterogeneity in study designs (e.g., duration, immobilized limb, experience level of participants, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…Manual curation of literature and bioinformatics data was performed by one author (D.A.B. ), with experience in the extraction of kinase-substrate interactions from the literature [55,56], who also participated in the data extraction for the development of the Kinase Enrichment Analysis version 2 by the Ma'ayan Laboratory (capstone project) [57]. A second author, with extensive experience in bioinformatics and systems biology (D.A.F.…”
Section: Manual Curation and Bioinformatics-assisted Reviewmentioning
confidence: 99%